Uterine smooth muscle tumours and the role of Ki67 expression in determining their biological behaviour - K. R., Krishna Priya; Saldanha, Prema; Shariff, M. H. (International Journal of Research in Medical Sciences, 2025)
Background: Uterine smooth muscle tumours include leiomyoma, intravenous leiomyoma, metastasizing leiomyoma, smooth muscle tumour of uncertain malignant potential (STUMP) and leiomyosarcoma (LMS). Diagnosis primarily relies on histopathological features. In cases with overlapping morphological findings, immunohistochemical markers can help in differentiating benign and malignant lesions. This study evaluates the role of Ki67 immunohistochemical expression in determining the biological behaviour of uterine smooth muscle tumours. Methods: In this study a total of 58 cases of uterine smooth muscle tumours were analysed. Gross findings were observed. The microscopic evaluation was done on formalin fixed paraffin embedded sections and haematoxylin and eosin-stained slides. This was followed by Ki67 staining by immunohistochemistry and was graded depending on percentage of nuclear expression. Association of Ki67 grade with gross and microscopic findings were determined. Results: Among 58 tumours, 52 (90%) were leiomyomas, 3 (5%) STUMPs, and 3 (5%) LMS. Most patients were between 41 and 50 years of age, with menorrhagia being the most common presenting complaint. Ki67 expression was low (86.2%) in all leiomyomas, consistently high in LMS and showed variable levels in STUMP. Ki67 levels demonstrated a significant association with mitotic activity, necrosis and cytologic atypia (p<0.05), but did not correlate with tumour size and secondary changes. Conclusions: Combining histopathology with Ki67 immunostaining improves diagnostic efficacy in uterine smooth muscle tumours and thus contributes to a more effective clinical management.